Positive pole piece, secondary battery and electric device
By controlling the content of manganese element, hydrogen ion growth characteristics and Al peak strength in the positive electrode active material, the problem of manganese ion dissolution of LMFP positive electrode material at high temperatures is solved, the gas production and internal resistance performance of the battery is improved, and the battery life is extended.
Patent Information
- Application Number
- CN202411936439.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing lithium manganese iron phosphate (LMFP) cathode materials are prone to manganese ion dissolution problems in high temperature environments, resulting in increased gas production of batteries and increased internal resistance, thereby reducing the battery charge and discharge efficiency and life.
By comprehensively controlling the content of manganese element in the positive electrode active material, the hydrogen ion growth characteristics of the positive electrode sheet, and the peak-to-peak intensity of the Al peak-to-peak at different depths of the electrode sheet, the relationship formula of 0.08≤(A×h)/IA1≤27 is met, so as to improve the gas production problem of the secondary battery and reduce the internal resistance growth rate.
The gas production problem of secondary batteries containing the positive electrode sheet is significantly improved, and the internal resistance growth rate is maintained after circulation, extending the service life of the battery.
Smart Images

Figure CN119725391A_ABST
Abstract
Description
[0001] This application is a divisional application of CN 118969964 A (filing date is October 17, 2024, application number is 202411449883.4, and the name of the invention is a positive electrode plate, secondary battery and electrical device). Technical Field
[0002] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0003] Lithium manganese iron phosphate (LMFP) cathode material has attracted wide attention in the field of electric vehicles and portable electronic devices due to its high energy density. Compared with lithium iron phosphate (LFP), LMFP increases the theoretical energy density of the battery by introducing manganese elements, making the battery have a longer battery life.
[0004] However, the increase in manganese content brings about the problem of manganese dissolution, especially in high temperature environments, where the dissolution of manganese ions may be aggravated. Manganese dissolution not only causes gas to be generated inside the battery, increasing the risk of battery expansion, but also forms deposits, which form inside the battery, increase the internal resistance of the battery, and reduce the battery's charge and discharge efficiency and life.
[0005] Therefore, it is necessary to provide a positive electrode plate that improves the gas generation problem and reduces the internal resistance. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a positive electrode plate, a secondary battery and an electrical device. By comprehensively controlling the manganese content in the positive electrode active material, the hydrogen ion growth characteristics of the positive electrode plate and the Al peak intensity at different depths of the plate, the gas production problem of the secondary battery containing the positive electrode plate is greatly improved, and the internal resistance growth rate of the battery after cycling is low.
[0007] To achieve the above object, in a first aspect of the present invention, the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a manganese-containing phosphate material;
[0008] The positive electrode sheet satisfies the following relationship:
[0009] 0.08≤(A×h) / I Al ≤27;
[0010] Wherein, A is the molar content of manganese element in the positive electrode active material to the transition metal element, in mol%;
[0011] H is the positive electrode sheet immersed in the mixed solution at 60°C T 1 h to T 2 h is the growth rate of hydrogen ion content, T 2 -T 1 =72, T 1 >0; the mixed solution contains an organic solvent and a lithium salt, and the unit of H is %;
[0012] I Al =I 2 -I 1 , the I 1 When the surface of the positive electrode is subjected to X-ray photoelectron spectroscopy (XPS) analysis, the peak intensity of the characteristic peak of the aluminum element in the XPS diagram; 2 The peak intensity of the characteristic peak of aluminum element in the XPS graph is shown in Figure 1 after the positive electrode sheet is etched at an etching depth of 50 nm. 1 ,I 2 and I Al The unit is counts / s.
[0013] As a preferred embodiment of the present invention, the positive electrode sheet satisfies the following relationship: 0.16≤(A×h) / I Al ≤4.5.
[0014] As a preferred embodiment of the present invention, the range of A is 50 to 95 mol%.
[0015] As a further preferred embodiment of the present invention, the range of A is 55 to 85 mol%.
[0016] As a preferred embodiment of the present invention, the range of H is 12-42%.
[0017] As a further preferred embodiment of the present invention, the range of H is 15-35%.
[0018] As a preferred embodiment of the present invention, the I Al The range is 100~9000counts / s.
[0019] As a further preferred embodiment of the present invention, the I Al The range is 600~7000counts / s.
[0020] As a preferred embodiment of the present invention, the I 1 The range is 100~12800counts / s.
[0021] As a preferred embodiment of the present invention, the positive electrode active material includes lithium manganese iron phosphate material.
[0022] As a preferred embodiment of the present invention, the average particle size of the lithium manganese iron phosphate material is 30 to 400 nm.
[0023] As a preferred embodiment of the present invention, the mixed solution comprises ethylene carbonate, ethyl methyl carbonate and lithium perchlorate, wherein the volume ratio of ethylene carbonate to ethyl methyl carbonate is 3:7, and the molar concentration of lithium perchlorate in the mixed solution is 1 mol / L.
[0024] In a second aspect of the present invention, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet is the above-mentioned positive electrode sheet.
[0025] In a third aspect of the present invention, the present invention provides an electrical device comprising the above-mentioned secondary battery.
[0026] The beneficial effects of the present invention are:
[0027] The present invention develops a positive electrode sheet, a secondary battery and an electric device. By comprehensively controlling the manganese content in the positive electrode active material, the hydrogen ion growth characteristics of the positive electrode sheet and the Al peak intensity at different depths of the sheet, the gas generation problem of the secondary battery containing the positive electrode sheet is greatly improved, and the internal resistance growth rate of the battery after cycling is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XPS graph of the positive electrode sheet of Example 6. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0031] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0032] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0033] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0034] Positive electrode
[0035] An embodiment of the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a manganese-containing phosphate material;
[0036] The positive electrode sheet satisfies the following relationship:
[0037] 0.08≤(A×H) / I Al ≤27;
[0038] Wherein, A is the molar content of manganese element in the positive electrode active material to the transition metal element, in mol%;
[0039] H is the positive electrode sheet immersed in the mixed solution at 60°C T 1 h to T 2 h is the growth rate of hydrogen ion content, T 2 -T 1 =72, T 1 >0; the mixed solution contains an organic solvent and a lithium salt, and the unit of H is %;
[0040] I Al =I 2 -I 1 , the I 1 When the surface of the positive electrode is subjected to XPS analysis, the peak intensity of the characteristic peak of the aluminum element in the XPS diagram; 2 The peak intensity of the characteristic peak of aluminum element in the XPS graph is shown in Figure 1 after the positive electrode sheet is etched at an etching depth of 50 nm. 1 ,I 2 and I Al The unit is counts / s.
[0041] The present invention greatly improves the gas production problem of a secondary battery containing the positive electrode sheet by comprehensively controlling the manganese content in the positive electrode active material, the hydrogen ion growth rate of the positive electrode sheet, and the Al peak intensity at different depths of the positive electrode sheet, and the internal resistance growth rate of the battery after cycling is low.
[0042] The present invention has found that a certain amount of aluminum (Al) in the positive electrode sheet helps to improve the gas production inside the battery. During the first charging process of the battery, the Al in the positive electrode sheet will participate in the chemical reaction earlier than the manganese element (Mn), promoting the formation of a solid electrolyte interface film (CEI film) on the surface of the positive electrode sheet. The rapid formation of the CEI film can effectively protect the positive electrode before manganese dissolves, thereby greatly reducing the side reactions between the positive electrode active material and the electrolyte and reducing the generation of gas inside the battery. However, the Al content in the surface layer of the positive electrode sheet (mainly the CE I film) should not be too high. The Al located in the surface layer of the positive electrode sheet may dissolve into the negative electrode sheet and participate in the formation of the negative electrode solid electrolyte interface film (SE I film). When the Al content is too high, it may cause the membrane impedance of the negative electrode SEI film to increase, thereby increasing the internal resistance of the battery.
[0043] In XPS analysis, the position of the characteristic peak of an element is mainly determined by binding energy, and the position of the characteristic peak is generally related to the element type, valence state, structure and test environment. For the positive electrode of the present invention, the characteristic peak of the aluminum element generally appears in the XPS graph with a binding energy of 60 to 90 eV. The peak intensity of the characteristic peak of the aluminum element in the XPS graph can reflect the relative content of Al at that position. Al In order to adjust the peak intensity difference of Al peak at different etching depths of the positive electrode sheet, the present invention adjusts I Al The size of Al is controlled, that is, the content distribution of Al at different depths of the positive electrode sheet is controlled, so as to improve the gas production phenomenon of the battery and also keep the internal resistance of the battery low.
[0044] H is the growth rate of the hydrogen ion content of the positive electrode plate when immersed in a mixed solution containing lithium perchlorate. The positive electrode plate is immersed in a mixed solution containing a lithium salt, and the positive electrode active material reacts with the mixed solution at the interface to generate hydrogen ions. The greater the growth rate of the hydrogen ion content during the impregnation process, the higher the degree of the interfacial reaction. The degree of particle passivation of the positive electrode active material is an important factor affecting the above-mentioned reaction degree. Therefore, the hydrogen ion growth rate in the present invention reflects the degree of particle passivation of the positive electrode active material to a certain extent. By controlling the size of the H value, adjusting the degree of passivation, and utilizing the passivation effect to reduce the oxidizability of the positive electrode active material, the positive electrode plate can be protected, manganese dissolution can be reduced, the gas production of the battery can be improved, and the internal resistance of the battery can be reduced. However, the H value should not be too low. A too low H value may mean excessive passivation, which leads to obstruction of electron transmission inside the positive electrode plate and an increase in the internal resistance of the battery.
[0045] The size of the H value is related to many factors, such as the particle structure of the positive electrode active material, the particle coating, the additive composition of the battery electrolyte, and the doping elements and content of the positive electrode active material. In other words, the content of Al and Mn in the positive electrode sheet will affect the size of the H value. Therefore, the present invention comprehensively controls the manganese content in the positive electrode active material, the hydrogen ion growth rate of the positive electrode sheet, and the Al peak intensity at different depths of the positive electrode sheet, and controls it to meet 0.08≤(A×H) / I Al ≤27, which improves the gas production problem of the secondary battery containing the positive electrode plate, and the internal resistance growth rate of the battery after cycling is low.
[0046] When(A×H) / I Al When the value of is too small, less than 0.08, there may be excessive passivation or too high aluminum content in the surface layer of the positive electrode, resulting in too high an increase in the internal resistance of the battery. Al When the value is too high, greater than 27, it may cause serious gas production of the battery and a high internal resistance growth rate.
[0047] Exemplarily, in the present invention, (A×H) / I Al The value of can be 0.08, 0.10, 0.15, 0.20, 0.50, 1.0, 2.0, 5.0, 10.0, 15.0, 20.0, 25.0, 25.5, 26.0, 26.5, 26.8, 26.85, 26.90, 26.95, 27.0, or it can be an interval formed by any two of the above values.
[0048] In one embodiment, the positive electrode sheet satisfies the following relationship: 0.16≤(A×h) / I Al ≤4.5.
[0049] The present invention further studies and finds that when the positive electrode plate is within the above preferred range, the gas production and internal resistance growth rate of the battery are better overall.
[0050] In one embodiment, the range of A is 50-95 mol%, for example, A can be 50 mol%, 55 mol%, 60 mol%, 70 mol%, 80 mol%, 90 mol%, or 95 mol%.
[0051] In a preferred embodiment, the range of A is 55 to 85 mol%.
[0052] In the present invention, the positive electrode active material with a higher manganese content is preferred, which helps the battery have a better energy density. However, the A value should not be too high. On the one hand, a too high A value will increase the possibility of manganese dissolution, and on the other hand, it will affect the passivation effect of the positive electrode, deteriorate the gas production of the battery, and also increase the internal resistance of the battery.
[0053] The present invention does not limit the detection method of A, and those skilled in the art can detect the molar content of manganese in the phosphate material according to conventional technical means, such as ICP testing.
[0054] Exemplarily, A can be detected by the following method:
[0055] The battery in an empty state is disassembled to obtain the positive electrode plate, which is then processed to obtain the positive electrode active material powder. The molar content of manganese element in the positive electrode active material as a percentage of the transition metal element is obtained through ICP testing.
[0056] In one embodiment, the range of H is 12-42%, for example, H can be 12%, 15%, 18%, 25%, 30%, 35%, 38%, 40%, or 42%.
[0057] In one preferred embodiment, the range of H is 15-35%.
[0058] The H value reflects the degree of passivation of the positive electrode active material, which is affected by many factors, such as the particle structure, particle size, coating thickness, coating integrity, and coating amount of the positive electrode active material; the composition of the additives in the battery electrolyte, whether it contains additives that promote film formation and passivation; the doping elements and content in the bulk phase of the positive electrode active material, etc. If the H value is within the above preferred range, it means that the passivation effect of the positive electrode active material is appropriate, which can effectively improve the gas production of the battery without causing excessive increase in the internal resistance of the battery.
[0059] In one embodiment, the mixed solution includes ethylene carbonate (EC), ethyl methyl carbonate (EMC) and lithium perchlorate, wherein the volume ratio of ethylene carbonate to ethyl methyl carbonate is 3:7, and the molar concentration of lithium perchlorate in the mixed solution is 1 mol / L.
[0060] When the above-mentioned mixed solution is used, the positive electrode plate is immersed in the mixed solution, and the lithium salt and the solvent (EC, EMC) react to form a solvation structure, which promotes the interface reaction between the solvent and the positive electrode active material, and the solvent reacts and dehydrogenates to produce hydrogen ions. As the immersion time increases, the hydrogen ion content in the mixed solution increases. Lithium perchlorate, as a relatively stable lithium salt, helps to detect the H value more accurately.
[0061] Exemplarily, H can be detected by the following method:
[0062] The fully charged battery was disassembled to obtain the positive electrode sheet in the fully charged state. After drying at 80° C. for 4 h, the positive electrode sheet was obtained. The positive electrode sheet was cut into 7 cm×7 cm pieces to be tested.
[0063] At a test temperature of 60°C, immerse the electrode to be tested in 20 ml of a mixed solution consisting of ethylene carbonate, ethyl methyl carbonate and lithium perchlorate, wherein the volume ratio of ethylene carbonate to ethyl methyl carbonate is 3:7, and the molar concentration of lithium perchlorate in the mixed solution is 1 mol / L;
[0064] When the electrode to be tested is immersed in the mixed solution for 48 hours, the hydrogen ion content in the mixed solution is detected and recorded as H 1 ppm; When the electrode to be tested is immersed in the mixed solution for another 72 hours, the hydrogen ion content in the mixed solution is tested again, which is recorded as H 2 ppm;
[0065] The hydrogen ion content can be tested by acid-base titration;
[0066] Calculate the growth rate of hydrogen ion content when the positive electrode is immersed in a mixed solution containing perchloric acid H = (H 2 -H 1 ) / H 1 × 100%. The hydrogen ion content of the electrode to be tested when immersed in the mixed solution for 48 hours is taken as the initial hydrogen ion content, which takes into account the process of full wetting of the mixed solution and the positive electrode.
[0067] In one embodiment, the I Al The range is 100 to 9000 counts / s. AlIt can be 100 counts / s, 200 counts / s, 500 counts / s, 1000 counts / s, 3000 counts / s, 5000 counts / s, 8000 counts / s, 8500 counts / s, 9000 counts / s.
[0068] In one preferred embodiment, the I Al The range is 600~7000counts / s.
[0069] In one embodiment, the I 1 The range is 100~12800counts / s.
[0070] I Al The value of is greater than 0, indicating that Al is more present in the positive electrode active material layer rather than in the CEI film layer. Al Within the above preferred range, the distribution of Al is more suitable, and there is a sufficient amount of aluminum in the positive electrode active material layer in the middle position of the positive electrode plate (etching depth 50nm), which helps to effectively improve the gas production of the battery, and the aluminum content in the surface layer of the positive electrode plate (etching depth 0nm) is low, avoiding the degradation of the internal resistance of the battery.
[0071] Because I 1 ,I 2 It is impossible to be a negative number, so it can be inferred that I Al When the value is too low, it means that I 2 The value of is very small (I 1 The value of is relatively smaller), or I 1 ,I 2 The values are very close. 1 ,I 2 The value of is too small, indicating that the Al content in the positive electrode is low, and the improvement of the battery gas production problem is not obvious enough; 1 ,I 2 The values of are very close, indicating that the difference in Al content between the middle and surface of the positive electrode is too small, which may lead to a high internal resistance of the battery. Al The value is higher than 9000 counts / s, which means that the Al content in the middle of the positive electrode (that is, I 2 ) is not less than 9000 counts / s. The overall Al content of the positive electrode is too high, which may lead to a large increase in the internal resistance of the battery during the cycle.
[0072] I Al The value of can be controlled by adding doping elements during the preparation of the positive electrode active material, or by adding aluminum elements during the preparation of the positive electrode sheet.
[0073] For example, I Al The following methods can be used for detection:
[0074] The battery is disassembled to obtain the positive electrode sheet, and the positive electrode sheet is dried to obtain the electrode sheet to be tested; XPS analysis is performed on the surface of the electrode sheet to be tested and at an etching depth of 50 nm to obtain the difference in peak intensity of the characteristic peak of the aluminum element.
[0075] In one embodiment, the positive electrode active material includes lithium manganese iron phosphate material.
[0076] The lithium manganese iron phosphate material includes at least one of lithium manganese iron phosphate (LMFP), lithium manganese iron phosphate containing doping elements, and lithium manganese iron phosphate containing a coating layer.
[0077] In one embodiment, the average particle size of the lithium manganese iron phosphate material is 30 to 400 nm.
[0078] The lithium iron manganese phosphate material can be a single particle or an agglomerate composed of primary particles. When the lithium iron manganese phosphate material is a single particle, the average particle size of the lithium iron manganese phosphate material refers to the average particle size of the single particle; when the lithium iron manganese phosphate material is an agglomerate, the average particle size of the lithium iron manganese phosphate material refers to the average particle size of the primary particles.
[0079] The doping element may be aluminum.
[0080] The coating layer is coated on the surface of the LMFP particles, and the coating layer may be a carbon layer.
[0081] In the present invention, the preparation method of LMFP is not limited, and those skilled in the art can prepare LMFP according to conventional technical means.
[0082] Exemplarily, the preparation method of LMFP may include the following steps:
[0083] Mixing a manganese source, an iron source, a phosphorus source and a lithium source in a certain molar ratio and grinding them;
[0084] The ground product is spray dried and then sintered in an atmosphere with an oxygen concentration of less than 150 ppm to obtain LMFP.
[0085] According to the needs, the grinding-spray drying-sintering process can be performed multiple times when preparing LMFP. For example, the manganese source, iron source, phosphorus source, and lithium source can be mixed, ground once, spray dried once, and then sintered once in an atmosphere with an oxygen concentration of less than 150 ppm; the product of the first sintering is ground twice, spray dried twice, and then sintered twice in an atmosphere with an oxygen concentration of less than 150 ppm; and then post-processed to obtain LMFP.
[0086] The lithium source may include at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate or lithium acetate.
[0087] The phosphorus source may include at least one of diammonium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate, or lithium phosphate.
[0088] The iron source may include at least one of ferrous oxalate, ferric hydroxide, ferrous hydroxide, ferric phosphate, ferrous phosphate, ferric acetate, ferrous acetate, ferric carbonate, ferrous carbonate, ferrous oxide, ferrous oxide or ferric oxalate.
[0089] The manganese source may include at least one of manganese carbonate, manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, or manganese acetate.
[0090] Ferromanganese phosphate can be selected to serve as a manganese source, an iron source and a phosphorus source at the same time; ferric phosphate can be selected to serve as an iron source and a phosphorus source at the same time.
[0091] When the LMFP also contains doping elements, a certain amount of the doping element source can be weighed and mixed with the manganese source, iron source, phosphorus source and lithium source for ball milling.
[0092] When the doping element is aluminum, the doping element source is an aluminum source. The aluminum source may include at least one of aluminum formate, aluminum acetate, aluminum glycolate, aluminum lactate, aluminum tartrate, aluminum oxalate, aluminum phosphate, aluminum hydrogen phosphate, aluminum dihydrogen phosphate, aluminum carbonate, aluminum oxide, aluminum hydroxide, aluminum fluoride, aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum bromide.
[0093] When the LMFP also contains a coating layer, a certain amount of raw materials for the coating layer can be weighed and mixed with a manganese source, an iron source, a phosphorus source, and a lithium source for ball milling.
[0094] When the coating layer is a carbon layer, the raw material of the coating layer is a carbon source, which may include at least one of glucose, sucrose, and polyethylene glycol.
[0095] In one embodiment, the positive electrode active material includes at least one of lithium iron phosphate and lithium nickel cobalt manganese oxide.
[0096] When lithium iron manganese phosphate material is compounded with other types of positive electrode materials (such as lithium iron phosphate or lithium nickel cobalt manganese oxide) as positive electrode active materials, when the positive electrode sheet satisfies 0.08≤(A×H) / I Al When ≤27, the secondary batteries using the positive electrode sheet have less gas production and lower cycle internal resistance growth rate.
[0097] In addition to the above-mentioned positive electrode active material, the positive electrode active material layer may further include a conductive agent and a binder.
[0098] The conductive agent can be used as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. In the present invention, there is no particular limitation on the type of the conductive agent. Specifically, the conductive agent can be at least one of carbon nanotubes, carbon black or graphene.
[0099] The binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. Specifically, the conductive agent can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.
[0100] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.
[0101] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art, for example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent to form a uniform positive electrode slurry, the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.
[0102] Secondary battery
[0103] An embodiment of the present invention provides a secondary battery, comprising the positive electrode sheet described above.
[0104] In addition to the positive electrode sheet, the electrochemical device also includes a negative electrode sheet, a separator and an electrolyte.
[0105] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material. For the negative electrode active material, the embodiment of the present invention does not specifically limit the type of the negative electrode active material, and can be selected according to actual needs. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, and silicon-carbon composites.
[0106] The diaphragm is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm can be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.
[0107] The electrolyte of the present invention can be any electrolyte suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte can generally include a lithium salt.
[0108] Specifically, the lithium salt includes lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (Li BF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (Li FS I), lithium bis(trifluoromethanesulfonyl)imide (Li TFSI), lithium trifluoromethanesulfonate (Li TFS), lithium difluorooxalatoborate (Li DFOB), lithium dioxalatoborate (Li BOB), lithium difluorophosphate (Li PO 2 F 2 ), lithium difluorobis(oxalate)phosphate (Li DFOP) and lithium tetrafluorooxalate)phosphate (Li TFOP). The concentration of the electrolyte in the electrolyte solution may be 0.5 to 5 mol / L.
[0109] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0110] Electrical devices
[0111] An embodiment of the present invention provides an electric device, comprising the secondary battery described above.
[0112] The electrical device serves as a power supply for the electrical device.
[0113] The electrical device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other energy forms, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0114] The present invention is further described below with specific embodiments:
[0115] Example 1
[0116] This embodiment provides a lithium ion battery, and the specific preparation method is as follows:
[0117] (1) Preparation of positive electrode sheet
[0118] S1. According to the molar ratio of n(Li):n(Mn+Fe):n(P)=1:1:1, and n(Mn):n(Fe)=75:25, accurately weigh Mn 3 O 4 、FePO 4 , LiH 2 PO 4 mixing to obtain a mixed material;
[0119] Then weigh the carbon source (75wt.% glucose and 25wt.% polyethylene glycol), and the aluminum source (Al 2 O 3 ), added to the mixture and subjected to the first ball milling, the first spraying and the first sintering to obtain a first sintered precursor;
[0120] Wherein: the aluminum source is weighed according to the molar ratio n(Al) / n(Mn)=6000ppm;
[0121] Wherein: the carbon source is weighed according to 5wt.% of the weight of the mixture;
[0122] The conditions for the first ball milling were: 500 rpm, 25 °C, 22 h;
[0123] The conditions for the first spraying were: spray pressure 0.65 MPa;
[0124] The conditions for the first sintering were: 500 °C, 10 h;
[0125] S2. A certain amount of carbon source (75wt.% glucose and 25wt.% polyethylene glycol) was weighed and mixed with the first calcined precursor, and then a second ball milling, a second spraying, and a second sintering were performed together. Then, the particles were crushed, sieved, and impurities were removed to obtain a lithium manganese iron phosphate material (lithium manganese iron phosphate with a carbon material layer on the surface) with an average particle size of 85.2nm. The lithium manganese iron phosphate material is the positive electrode active material;
[0126] Wherein: the amount of carbon source is adjusted to control the carbon coating amount of lithium manganese iron phosphate (the mass ratio of carbon material to lithium manganese iron phosphate material) to 2.8wt.%;
[0127] The conditions for the second ball milling were: 500 rpm, 25 °C, 22 h;
[0128] The conditions for the second spraying were: spray pressure 0.65 MPa;
[0129] The conditions for the second sintering are: 600°C, 10h.
[0130] S3. The positive electrode active material is mixed with a binder (PVDF) and a conductive agent (SP) in a mass ratio of 96:3:1, and dispersed in NMP to obtain a positive electrode slurry. Subsequently, the mixed positive electrode slurry is evenly coated on an aluminum foil, dried in a vacuum oven at 100°C, rolled, cut, and baked to obtain a positive electrode sheet.
[0131] (2) Preparation of negative electrode sheet
[0132] The negative electrode active material (artificial graphite), conductive agent (SP), and binder (carboxymethyl cellulose, CMC) are mixed in a mass ratio of 92:4:4, dispersed in deionized water to obtain a negative electrode slurry, and the negative electrode slurry is evenly coated on the negative electrode collector (copper foil), and the negative electrode collector coated with the negative electrode slurry is transferred to a vacuum environment in an oven for drying at 100°C, and then rolled, cut, and baked to obtain a negative electrode sheet.
[0133] (3) Preparation of electrolyte
[0134] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF 6 Dissolve in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0135] (4) Preparation of diaphragm
[0136] Polyethylene (PE) diaphragm is used.
[0137] (5) Preparation of batteries
[0138] The positive electrode sheet, separator and negative electrode sheet prepared above are wound to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.
[0139] Examples 2 to 9, Examples 11 to 18 and Comparative Examples 1 and 2
[0140] Examples 2 to 9, Examples 11 to 18 and Comparative Examples 1 and 2 respectively provide a lithium ion battery, and the specific preparation method is similar to that of Example 1, except that, in the preparation of the positive electrode sheet:
[0141] The values of n(Mn):n(Fe) and n(Al) / n(Mn) in S1 are shown in Table 1;
[0142] The time of the first ball milling is shown in Table 1;
[0143] In S2, after crushing and sieving, the average particle size of the lithium manganese iron phosphate material is adjusted to meet the requirements shown in Table 1; the amount of the carbon source is adjusted to control the carbon coating amount of the lithium manganese iron phosphate material to meet the requirements shown in Table 1; the time of the second ball milling is shown in Table 1;
[0144] For Example 3, step S2 has the following difference: after obtaining the lithium iron manganese phosphate material, the lithium iron manganese phosphate material and lithium iron phosphate are mixed in a mass ratio of 8:2 to obtain the positive electrode active material;
[0145] For Example 15, step S2 has the following differences: after obtaining the lithium iron manganese phosphate material, the lithium iron manganese phosphate material and the ternary material (LiNi 0.6 Co 0.2 Mn 0.2 O 2 ) are mixed in a mass ratio of 2:8 to obtain a positive electrode active material;
[0146] For Example 16, step S2 has the following difference: after obtaining the lithium iron manganese phosphate material, the lithium iron manganese phosphate material and the ternary material (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) are mixed in a mass ratio of 2:8 to obtain the positive electrode active material.
[0147] Example 10
[0148] Embodiment 10 provides a lithium ion battery, and the specific preparation method is similar to that of Embodiment 1, except that the positive electrode sheet is prepared according to the following method:
[0149] According to the molar ratio of n(Li):n(Mn+Fe):n(P)=1:1:1, and n(Mn):n(Fe)=56:44, accurately weigh Mn 3 O 4 、FePO 4 , LiH 2 PO 4 mixing to obtain a mixed material;
[0150] Then weigh the carbon source (75wt.% glucose and 25wt.% polyethylene glycol), and the aluminum source (Al 2 O 3 ), added to the mixture and subjected to the first ball milling, the first spraying and the first sintering, to obtain a lithium manganese iron phosphate material (lithium manganese iron phosphate with a carbon material layer coated on the surface) with an average particle size of 210 nm; (without multiple ball milling or multiple sintering), the lithium manganese iron phosphate material is the positive electrode active material;
[0151] Wherein: the aluminum source is weighed according to the molar ratio n(Al) / n(Mn)=7600ppm;
[0152] The amount of carbon source is adjusted to control the carbon coating amount of lithium manganese iron phosphate (the mass ratio of carbon material to lithium manganese iron phosphate material) to 2.0wt.%;
[0153] The conditions for the first ball milling were: 500 rpm, 25 °C, 24 h;
[0154] The conditions for the first spraying were: spray pressure 0.65 MPa;
[0155] The first sintering conditions were: 600 °C, 10 h;
[0156] The positive electrode active material is then mixed with a binder (PVDF) and a conductive agent (SP) in a mass ratio of 96:3:1 and dispersed in NMP to obtain a positive electrode slurry. Subsequently, the mixed positive electrode slurry is evenly coated on an aluminum foil, dried in a vacuum oven at 100°C, rolled, cut, and baked to obtain a positive electrode sheet.
[0157] Comparative Example 3
[0158] Comparative Example 3 provides a lithium ion battery, and the specific preparation method is similar to that of Example 1, except that in the preparation of the positive electrode sheet:
[0159] In S1, no aluminum source was added, and the values of n(Mn):n(Fe) were shown in Table 1; the time of the first ball milling was shown in Table 1;
[0160] In S2, after crushing and sieving, the average particle size of the lithium manganese iron phosphate material is adjusted to meet the requirements shown in Table 1; the amount of the carbon source is adjusted to control the carbon coating amount of the positive electrode active material to meet the requirements shown in Table 1; the time of the second ball milling is shown in Table 1;
[0161] S3 is the following steps:
[0162] S3. The positive electrode active material is mixed with a binder (PVDF) and a conductive agent (SP) in a mass ratio of 96:3:1, and dispersed in NMP to obtain a first positive electrode slurry; 1.2 wt.% Al is added to the first positive electrode slurry. 2 O 3 , obtaining a second positive electrode slurry;
[0163] The second positive electrode slurry is evenly coated on the aluminum foil, dried in a vacuum oven at 100° C., rolled, cut, and baked to obtain a positive electrode sheet.
[0164] The carbon coating amount of lithium manganese iron phosphate material is determined by the following method:
[0165] After being weighed by an electronic balance, the sample enters the combustion reaction pool. Under the condition of sufficient oxygen, it is heated and burned at high temperature by a high-frequency furnace to oxidize carbon into carbon dioxide. After filtering and drying, the gas enters the corresponding absorption pool to absorb the corresponding infrared radiation spectrum (carbon dioxide 4200nm), and then is converted into a corresponding electrical signal by the detector. This signal is collected by a computer, converted into a value proportional to carbon dioxide after linear correction, and then the values of the entire analysis process are accumulated. After the analysis is completed, the accumulated value is divided by the weighing value in the computer, and then multiplied by the correction coefficient to obtain the mass fraction of carbon in the sample, that is, the carbon coating amount (unit wt.%).
[0166] Table 1
[0167]
[0168]
[0169] The A, h and I of the positive electrode sheets in the lithium ion batteries prepared in the above examples and comparative examples are Al The detection method is as follows and the test results are shown in Table 2.
[0170] Detection method:
[0171] A: Disassemble the empty lithium-ion battery to obtain the positive electrode sheet. After drying at 80°C for 4 hours, place the positive electrode sheet in a sintering furnace at 400°C for 4 hours, and use a ceramic knife to scrape off the positive electrode active material powder;
[0172] Accurately weigh 0.5g of positive electrode active material powder, disperse it in 20ml of water, add 10ml of nitric acid, mix well and heat it. After the positive electrode active material powder is dissolved, dilute the material to 100ml with water to obtain a solution to be tested;
[0173] The solution to be tested was subjected to an ICP test, and the ICP test conditions were as follows: the element detection spectrum wavelength (Mn wavelength 257.61 nm) was selected, and appropriate ICP instrument working conditions were set according to the characteristics of the sample and the element to be detected, including a gas flow rate of 0.5 L / min and a power of 1150 W; the Mn content of the element was tested by ICP, and the molar content of manganese in the positive electrode active material as a percentage of the transition metal element was obtained, that is, the value of A, in mol%.
[0174] H: The lithium-ion battery is first discharged at a rate of 0.33C; then charged at a rate of 0.33C to a cut-off voltage of 4.25V, a cut-off current of 0.05C, and the battery reaches 100% SOC, i.e., a fully charged state; the battery in the fully charged state is disassembled to obtain the positive electrode sheet in the fully charged state, and after drying at 80°C for 4h, the positive electrode sheet is obtained, and the positive electrode sheet is cut into 7cm×7cm pieces to be tested;
[0175] At 60°C, the electrode to be tested was immersed in 20 ml of a mixed solution consisting of ethylene carbonate, ethyl methyl carbonate and perchloric acid, wherein the volume ratio of ethylene carbonate to ethyl methyl carbonate was 3:7, and the molar concentration of lithium perchlorate in the mixed solution was 1 mol / L.
[0176] When the electrode to be tested is immersed in the mixed solution for 48 hours, the hydrogen ion content in the mixed solution is detected and recorded as H 1 ppm; When the electrode to be tested is immersed in the mixed solution for another 72 hours, the hydrogen ion content in the mixed solution is tested again, which is recorded as H 2 ppm;
[0177] The hydrogen ion content (H 1 , H 2 ) is detected by the following method:
[0178] Triethylamine and ethyl methyl carbonate (EMC) are prepared into a 0.05 mol / L triethylamine titration solution; the mixed solution in which the positive electrode is immersed is taken as the test solution, 10 to 30 drops of methyl red are added thereto as an indicator, and the triethylamine titration solution is dripped into the test solution containing methyl red, and the amount of triethylamine titration solution is recorded when the test solution turns orange; then the hydrogen ion content is obtained according to the formula:
[0179] Hydrogen ion content = M × V × 20010 / m, the unit of hydrogen ion content is ppm;
[0180] Where: M is the concentration of triethylamine titration solution, unit: mol / L,
[0181] V is the volume of titrant consumed by triethylamine, in mL,
[0182] m is the mass of the solution to be tested, in g,
[0183] 20010=20.01×10 3 , 20.01 is the molecular weight of HF, and the fully charged positive electrode contains the electrolyte component LiPF 6 The positive electrode active material reacts with EC and EMC to dehydrogenate and forms a 6 HF is produced in the presence of, and the amount of HF represents hydrogen ions.
[0184] Calculate the growth rate of hydrogen ion content when the positive electrode is immersed in a mixed solution containing perchloric acid H = (H 2 -H 1 ) / H 1 ×100%.
[0185] I Al : Disassemble the battery to obtain the positive electrode sheet, dry the positive electrode sheet at 80°C for 4 hours to obtain the electrode sheet to be tested;
[0186] XPS analysis was performed on the surface of the electrode to be tested, and the peak intensity of the characteristic peak of aluminum element in the XPS graph was I 1 counts / s;
[0187] After etching the electrode to be tested with an etching depth of 50 nm, XPS analysis was performed, and the peak intensity of the characteristic peak of aluminum element in the XPS graph was I 2 counts / s;
[0188] The XPS analysis conditions are: using a 120W monochromatic Al Kα X-ray source; the energy resolution is less than or equal to 0.48eV; the test beam spot is 400 microns, and the instrument automatically supplements the test energy range according to the element to be tested; the etching treatment conditions are: using Ar ions for etching, and controlling the etching depth to 50nm by adjusting the etching rate or etching time, etc.
[0189] After the XPS analysis is completed, the instrument will automatically give the test results and read the I 1 and I 2 ;
[0190] Calculate I Al =I 2 -I 1 , I 1 ,I 2 and I AlThe unit is counts / s.
[0191] Figure 1 The XPS graph of the positive electrode of Example 1, wherein the lower line is the XPS spectrum obtained by performing XPS analysis on the surface of the electrode to be tested; the upper line is the XPS spectrum obtained by performing XPS analysis on the electrode to be tested after etching to a depth of 50 nm. Figure 1 In the figure, the characteristic peak of aluminum element is located at the binding energy of 84±1eV.
[0192] Table 2
[0193]
[0194]
[0195] The gas generation performance of the positive electrode sheets prepared in the above embodiments and comparative examples, and the internal resistance (DCR) growth rate of the lithium-ion batteries prepared in the embodiments and comparative examples were tested. The specific test method is as follows, and the test results are shown in Table 3.
[0196] (1) Gas production performance:
[0197] The positive electrode sheets, separators, and negative electrode sheets of the embodiments and comparative examples are prepared into soft-pack batteries through roll cutting, assembly, drying, and liquid injection processes;
[0198] Install the special container, electronic scale, a soft-pack battery, wire, bracket and formation device, and inject water into the special container until water overflows from the opening of the special container and the soft-pack battery is completely immersed in water;
[0199] When waiting for the overflow to stop, return the electronic scale to zero; proceed with the formation (formation process: charge to 2.4V at 0.02C, let stand for 10 minutes, discharge to 2V at 0.02C, let stand for 10 minutes, repeat this three times, then charge to 3.5V at 0.02C, let stand for 10 minutes, then charge to 4.25V at 0.1C). During the formation process, the gas generated inside the soft-pack battery causes the volume of the battery to expand continuously, causing the liquid in the special container to overflow continuously, so that the reading of the electronic scale changes at the same time, and the volume of water overflowing is also the volume of gas generated;
[0200] After the formation is completed, the reading on the electronic scale is the mass of liquid loss. The density of water is known; the gas production = mass of liquid loss / density of water, in milliliters (ml);
[0201] The soft-pack battery is subjected to constant capacity test (charged to 4.25V at a constant current rate of 1 / 3C, and charged at a constant voltage until the current is less than 0.05C, for more than 3 times, and the capacity of the battery is recorded to obtain the actual capacity of the soft-pack battery (in Ah);
[0202] The gas production performance of the positive electrode is evaluated by the gas production per unit capacity of the battery. The gas production per unit capacity = gas production / actual capacity (unit: ml / Ah).
[0203] (2) DCR growth rate:
[0204] The lithium-ion battery was charged to a constant capacity at 0.33C to 4.25V, the constant voltage cutoff current was 0.05C, and the charge was adjusted to 50% SOC at 0.33C. After standing for 2 hours, it was discharged at 1C at 50% SOC. The initial battery internal resistance was measured to obtain DCR. 1 ;
[0205] The lithium-ion battery was placed in a 55°C constant temperature box, and the lithium-ion battery was discharged at a constant current of 0.33C. Then, the battery was cycled in the constant temperature box at a charge and discharge test rate of 1C / 1C and a cycle voltage range of 2.5-4.25V for a total of 300 cycles.
[0206] After 300 cycles, the battery was discharged at 0.33C to 50% SOC, left to stand for 2 hours, and then discharged at 1C at 50% SOC. The internal resistance of the battery after the cycle was measured to obtain the DCR. 2 ;
[0207] The battery internal resistance test method is: take the voltage at the last second of static state as V0, the voltage after 18s discharge as V1, the current during discharge as I, DCR = (V0-V1) / I;
[0208] Calculate the DCR growth rate = (DCR 2 -DCR 1 ) / DCR 1 ×100%.
[0209] Table 3
[0210]
[0211]
[0212] According to the test results in Table 3, the lithium-ion batteries using the positive electrode sheets prepared in the embodiments of the present invention all have excellent gas production performance (gas production per unit volume ≤ 24.1 ml / Ah), and the internal resistance growth rate of the lithium-ion battery after cycling is low (DCR growth rate ≤ 65%).
[0213] According to Examples 1 to 6 and Examples 10 to 11, it can be seen that when the positive electrode sheet further satisfies 0.16≤(A×H) / I Al When ≤4.5, the overall performance of the battery is better, the gas production is relatively lower, and the internal resistance increase is relatively less.
[0214] It can be seen from Comparative Examples 1 to 3 that when the positive electrode sheet exceeds the technical solution of the present invention, it does not satisfy 0.08≤(A×H) / I Al When ≤27, it is difficult for the lithium-ion battery using the positive electrode sheet to have both good gas production performance and low internal resistance growth rate.
[0215] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, characterized in that: The positive electrode active material includes lithium iron manganese phosphate material; The positive electrode sheet satisfies the following relationship: 0.16≤(A×H) / I Al ≤14.83; Wherein, A is the molar content of manganese element in the positive electrode active material to the transition metal element, in mol%; H is the growth rate of hydrogen ion content of the positive electrode plate from T1 h to T2 h when it is immersed in the mixed solution at 60°C, T2-T1=72, T1>0; the mixed solution contains an organic solvent and a lithium salt, and the unit of H is %; I Al =I2-I1, wherein I1 is the peak intensity of the characteristic peak of aluminum element in the XPS diagram when the surface of the positive electrode is subjected to XPS analysis; wherein I2 is the peak intensity of the characteristic peak of aluminum element in the XPS diagram after the positive electrode is etched to a depth of 50 nm and then subjected to XPS analysis; I1, I2 and I Al The unit is counts / s.
2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode sheet satisfies the following relationship: 0.16≤(A×H) / I Al ≤4.
5.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The range of A is 50 to 95 mol%.
4. The positive electrode sheet according to claim 3, characterized in that: The range of A is 55 to 85 mol%.
5. The positive electrode sheet according to claim 1 or 2, characterized in that: The range of H is 12-42%.
6. The positive electrode sheet according to claim 5, characterized in that: The range of H is 15-35%.
7. The positive electrode sheet according to claim 1 or 2, characterized in that: I Al The range is 100~9000counts / s.
8. The positive electrode sheet according to claim 7, characterized in that: I Al The range is 600~7000counts / s.
9. The positive electrode sheet according to claim 1 or 2, characterized in that: The range of I1 is 100 to 12800 counts / s.
10. The positive electrode sheet according to claim 9, characterized in that: The average particle size of the lithium manganese iron phosphate material is 30 to 400 nm.
11. The positive electrode sheet according to claim 1, characterized in that: The mixed solution comprises ethylene carbonate, ethyl methyl carbonate and lithium perchlorate, wherein the volume ratio of ethylene carbonate to ethyl methyl carbonate is 3:7, and the molar concentration of lithium perchlorate in the mixed solution is 1 mol / L.
12. A secondary battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The positive electrode sheet is the positive electrode sheet according to any one of claims 1 to 11.
13. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 12.
Citation Information
Patent Citations
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN115020685A
Preparation method of multi-carbon-coated high-compaction lithium manganese iron phosphate
CN115231543A
Lithium manganese iron phosphate positive electrode material and preparation method thereof
CN116873892A
Positive pole piece, electrochemical device comprising positive pole piece and electronic device
CN116960276A
Lithium ion battery
CN117497828A
Cited By
Positive electrode sheet, secondary battery, and electric device
WO2026081445A1